IMPLEMENTASI PEMENUHAN HAK PELAYANAN KESEHATAN BAGI TAHANAN DAN NARAPIDANA DI RUTAN KELAS IIB BANTUL - Muhammad Faris Humam; Ali Muhammad (Jurnal Komunikasi Hukum, 2024)
Fulfillment of health service rights for prisoners and convicts is one of the overall rights that must be fulfilled and has been regulated in laws and regulations. The purpose of this study was to determine the implementation of the fulfillment of health service rights for prisoners and convicts at the Primary Clinic of Rutan Class IIB Bantul Prison, along with its legal analysis. The research method used is a qualitative research method with an empirical legal approach. The location of the research is the Primary Clinic of Rutan Class IIB Bantul Prison. The population of this study were employees of Rutan Class IIB Bantul Prison, especially the health workers. The results of this study showed that so far the implementation of the fulfillment of health service rights for prisoners and convicts and related to laws and regulations has been going well. However, there are still obstacles in the absence of clinic accreditation and considerations regarding the need for medical personnel with permanent status. In addition, further research is still needed in the future.